(untitled) (Latakia University Journal -Medical Sciences Series, 2022)
In the recent years, there has been a significant development in the treatment of Hodgkin’s lymphoma, which have significantly improved patients’ survival. However, determining the type and intensity of the appropriate treatment protocol for each patient is as important as developing new and advanced treatments. It becomes clear to us the importance of developing prognostic systems to coincide with the development of treatments. International prognostic score (IPS) is the most common prognostic indicator in Hodgkin’s lymphoma, used in many Western countries. Hence, the objective of our research is to verify the utility of IPS in predicting treatment response in our local patients of both stages of disease (Early, advanced). According to our research, IPS showed a poor ability to predict response to treatment in early stage disease (P value = .663), but it showed high efficiency in advanced disease (P value = .039) and (sensitivity 81.8%, negative predictive value 90%). It becomes clear the importance of introducing IPS as a routine procedure to predict a complete response to ABVD in patients newly diagnosed with advanced Hodgkin Lymphoma. We also recommend re-evaluating the factors that constitute IPS and re-evaluating their threshold values in order to make this indicator more relevant.